Non-Invasive performance measurement in combat sports - Behendi, S. K.; Morgan, S.; Fookes, C. B. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
Computer vision offers a growing capacity to detect, and classify actions in a large range of sports. Since combat sports are highly dynamic and physically demanding, it is difficult to measure features of performance from competition in a safe and practical way. Also, coaches frequently wish to measure the performance characteristics of other competitors. For these reasons it is desirable to be able to measure features of competitive performance without using sensors or physical devices. We present a non-invasive method for extracting pose and features of behaviour in boxing using vision cameras and time of flight sensors. We demonstrate that body parts can be reliably located, which allow punching actions to be detected. Those data can then visualised in a way that allows coaches to analysis behaviour.